A fossil chrysochlorid skull in the Ditsong National Museum of Natural History: Robert Broom’s missing specimen unearthed? - Mason, Matthew J.; Bennett, Nigel C.; Pickford, Martin (Evolutionary Studies Institute, 2019)
An unlabelled, fossilized skull of a golden mole from the Ditsong National Museum of Natural History, Pretoria, was examined through micro-computed tomography. Reconstructions show that the species in question has alveoli for nine teeth in each upper jaw, although only six teeth in total remain. The skull resembles those of the extant chrysochlorids Amblysomus and Calcochloris, which also have nine teeth, but in most respects it is closer to Amblysomus. The ear region, examined in detail, also proved to be very similar to that of Amblysomus. Damage to the teeth and palate are consistent with the brief descriptions of a fossil golden mole skull first mentioned by Robert Broom in 1948. This specimen, dating from the Plio-Pleistocene and provisionally identified as Proamblysomus antiquus, subsequently went missing. We argue that the skull described here is Broom’s lost specimen, but whether this fossil species really deserves generic distinction from extant groups remains unclear.
Keywords: golden mole; chrysochloridae; Afrotheria; Proamblysomus; inner ear; malleus